2021
DOI: 10.15414/jmbfs.4292
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Content and Antioxidant Activity of Slovak Varietal Wines of Muscat Type

Abstract: Grapes and wine are important sources of antioxidants in human diet. Phenolic substances contained in grapevine berries belong to an important group of natural substances that get into wine in the process of wine making. Polyphenols and flavonoids are primarily accountable for the colour and taste of the wine, they affect the perception of bitterness and acerbity. They also have antioxidant properties, thus have a positive effect on human health. Health benefits of polyphenolic substances from wine may be asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…In comparison with the chardonnay wines from Montenegro (TPC 226 mg GAE L −1 ) [47], the content in Slovak chardonnay wines was higher in more than 100 mg GAE L −1 . Our results are also in agreement with experiments by Bajčan et al [30] and Čéryová et al [31], who examined the antioxidant activity, total phenolic and flavonoid contents in monovarietal wines of Welschriesling, chardonnay. According to their results, Slovak white wines were high in polyphenols (average content was 303.2 mg GAE.L−1 in Welschriesling, resp.…”
Section: Influence Of Varietysupporting
confidence: 93%
See 2 more Smart Citations
“…In comparison with the chardonnay wines from Montenegro (TPC 226 mg GAE L −1 ) [47], the content in Slovak chardonnay wines was higher in more than 100 mg GAE L −1 . Our results are also in agreement with experiments by Bajčan et al [30] and Čéryová et al [31], who examined the antioxidant activity, total phenolic and flavonoid contents in monovarietal wines of Welschriesling, chardonnay. According to their results, Slovak white wines were high in polyphenols (average content was 303.2 mg GAE.L−1 in Welschriesling, resp.…”
Section: Influence Of Varietysupporting
confidence: 93%
“…In our study, all wines presented relatively high values for the antioxidant activity, ranged between 51.06 and 72.53% of inhibition of DPPH (average: 63.30% for chardonnay, 58.62% for pinot blanc and 64.45 for pinot gris wines). Our results for antioxidant activity were correlated with previously published data for white wines [30,31,48]. According to several studies, polyphenolic compounds have shown a different behaviour towards DPPH free radical, both in terms of capacity and rate of scavenging [49,50].…”
Section: Influence Of Varietysupporting
confidence: 90%
See 1 more Smart Citation
“…The TPC content in white wine was determined by Mitrevska et al (2020) as 169.48 to 434.27 mg•L −1 in studied samples of white wine from north Macedonia [31]. Čeryová (2021) examined muscat cultivars of grapevines from Slovenia, determining a content of 226.80 to 568.30 mg•L −1 [32]. Snopek et al (2018) determined values of 203.06 (Riesling) up to 445.45 mg GAE•L −1 in white wine originating from the territory of Moravia [8].…”
Section: Impact Of Sulfur Dioxide Addition On Total Phenolic Content ...mentioning
confidence: 99%